The Value-Added Analysis of Intellectual Capital for Banking Financial Performance - Setyowati, Tupi; Jamilah, Jamilah (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
This study was conducted to see how intellectual capital (IC) affects company performance (ROA)by entering the size variable in its calculations. This study also analyzes how much financial performancechanges occur as an effect of the efficiency of the use of capital employees (CEE), the efficiencyof using Structural Capital (SCE), and the partial efficiency of using Human Capital (HCE).Research was conducted on conventional banking in Indonesia for the period 2013 - 2017. Theresearch data was obtained from the official website of the Indonesia Stock Exchange (IDX). Thisstudy found that VAIC had a significant positive effect on ROA, and from the three IC components itturned out that the CEE component had the greatest influence on ROA